Model-based Hypothesis Engineering for Supporting Adaptation to Uncertain Customer Needs - Gottschalk, Sebastian; Yigitbas, Enes; Engels, Gregor (Business Modeling and Software Design)
To build successful products, the developers have to adapt their product features and business models to uncertain customer needs. This adaptation is part of the research discipline of Hypotheses Engineering (HE) where customer needs can be seen as hypotheses that need to be tested iteratively by conducting experiments together with the customer. So far, modeling support and associated traceability of this iterative process are missing. Both, in turn, are important to document the adaptation to the customer needs and identify experiments that provide most evidence to the customer needs. To target this issue, we introduce a model-based HE approach with a twofold contribution: First, we develop a modeling language that models hypotheses and experiments as interrelated hierarchies together with a mapping between them. While the hypotheses are labeled with a score level of their current evidence, the experiments are labeled with a score level of maximum evidence that can be achieved during conduction. Second, we provide an iterative process to determine experiments that offer the most evidence improvement to the modeled hypotheses. We illustrate the usefulness of the approach with an example of testing the business model of a mobile application.
Keywords: Hypothesis Engineering; Model-based; Customer Need Adaptation; Business Model; Product Features

Stress state dependent damage modeling of self-pierce riveting process simulation using GISSMO damage model - Otroshi, Mortaza; Rossel, Moritz; Meschut, Gerson (Journal of Advanced Joining Processes)
Keywords: Self-pierce riveting; Ductile fracture; Damage modeling; GISSMO damage model

Motivierende Lernzugänge als Ausgangspunkt der Professionalisierung angehender Lehrer_innen - Caruso, Carina; Adammek, Christine; Bonanati, Sabrina; Wiescholek, Sybille (Herausforderung Lehrer*innenbildung - Zeitschrift Zur Konzeption, Gestaltung Und Diskussion)
Im Artikel werden drei verschiedene Lernzugänge (kom-petenzorientiertes, ästhetisches und biographisches Lernen) vorgestellt und aus theoretischer Perspektive deren motivierender Gehalt für selbstreguliertes Lernen in Praxisphasen des Lehramtsstudiumsherausgearbeitet. Als theoretische Grund-lage dient die Selbstbestimmungstheorie als zentrale motivationale Theorie zur Erklärung selbstbestimmten Handelns.
Keywords: ästhetische Forschung; Biographiearbeit; Praxissemester; Professionalisierung; selbstreguliertes Lernen; Motivation / aesthetic research; biographical work; long-term internship; profes-sionalization; self-regulated learning; motivation

Influence of the process temperature on the forming behaviour and the friction during bulk forming of high nitrogen steel
Due to the trend towards lightweight design in car body development mechanical joining technologies become increasingly important. These techniques allow for the joining of dissimilar materials and thus enable multi-material design, while thermic joining methods reach their limits. Semi-tubular self-piercing riveting is an important mechanical joining technology. The rivet production, however, is costly and time-consuming, as the process consists of several process steps including the heat treatment and coating of the rivets in order to achieve an adequate strength and corrosion resistance. The use of high nitrogen steel as rivet material leads to the possibility of reducing process steps and hence increasing the efficiency of the process. However, the high tool loads being expected due to the high strain hardening of the material are a major challenge during the rivet production. Thus, there is a need for appropriate forming strategies, such as the manufacturing of the rivets at elevated temperatures. Prior investigations led to the conclusion that forming already at 200 °C results in a distinct reduction of the yield strength. To create a deeper understanding of the forming behaviour of high nitrogen steel at elevated temperatures, compression tests were conducted in a temperature range between room temperature and 200 °C. The determined true stress – true strain curves are the basis for the further process and tool design of the rivet production. Another key factor for the rivet manufacturing at elevated temperatures is the influence of the process temperature on the tribological conditions. For this reason, ring compression tests at room temperature and 200 °C are carried out. The friction factors are determined on the basis of calibration curves resulting from the numerical analysis of the ring compression process. The investigations indicate that the friction factor at 200 °C is significantly higher compared to room temperature. This essential fact has to be taken into account for the process and tool design for the rivet production using high nitrogen steel.
Keywords: High nitrogen steel; Self-piercing riveting; Joining by forming; Bulk forming; Strain hardening

Improvement of a rivet geometry for the self-piercing riveting of high-strength steel and multi-material joints - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Production Engineering)
As a result of lightweight design, increased use is being made of high-strength steel and aluminium in car bodies. Self-piercing riveting is an established technique for joining these materials. The dissimilar properties of the two materials have led to a number of different rivet geometries in the past. Each rivet geometry fulfils the requirements of the materials within a limited range. In the present investigation, an improved rivet geometry is developed, which permits the reliable joining of two material combinations that could only be joined by two different rivet geometries up until now. Material combination 1 consists of high-strength steel on both sides, while material combination 2 comprises aluminium on the punch side and high-strength steel on the die side. The material flow and the stress and strain conditions prevailing during the joining process are analysed by means of numerical simulation. The rivet geometry is then improved step-by-step on the basis of this analysis. Finally, the improved rivet geometry is manufactured and the findings of the investigation are verified in experimental joining tests.
Keywords: Self-piercing riveting; Joining technology; Rivet geometry; Multi-material design; High-strength steel; Aluminium

Modellierung und experimentelle Charakterisierung der Wechselwirkung zwischen Ultraschallwandler und Flüssigkeit in kavitationsbasierten Prozessen - Bornmann, Peter
Ultraschall wird zur Effizienzsteigerung in verfahrenstechnischen Prozessen eingesetzt. Die Betriebsparamter der Ultraschallsysteme werden empirisch ermittelt, da derzeit keine systematische Analyse der Wechselwirkung zwischen Ultraschallwandler und Schallfeld sowie kein Verfahren zur Messung der Kavitationsaktivität ohne zusätzlichen Sensor existieren. Auf Basis einer experimentellen Analyse des betrachteten sonochemischen Reaktors wird ein Finite-Elemente-Modell aufgebaut, das die Wechselwirkung zwischen Schallfeld und Ultraschallwandler berücksichtigt. Die modellbasierte Analyse zeigt, dass wegen der akustischen Eigenschaften des Autoklavs nur direkt an der Sonotrode Kavitation entsteht. Die Wechselwirkung zwischen Ultraschallwandler und Schallfeld ermöglicht Aussagen über das Schallfeld und die Kavitationsaktivität auf Basis der Rückwirkung auf den Ultraschallwandler. Die lineare Schalldruckverteilung ermöglicht eine Prognose über die Verteilung von Kavitationszonen. Das beschriebene Modell liefert wertvolle Erkenntnisse für die Auslegung, Analyse und Skalierung sonochemischer Reaktoren. Auf Grund der rauen Prozessrandbedingungen ist die Applikation von Sensoren zur Überwachung der Kavitationsaktivität in vielen sonochemischen Prozessen nicht möglich. Zur prozessbegleitenden Messung der Kavitationsaktivität wird ein Verfahren entwickelt, das die Bewertung der Kavitationsaktivität durch Auswertung der Rückwirkung auf den Ultraschallwandler erlaubt. Das Messverfahren ermöglicht eine vorhersagbare und reproduzierbare Durchführung kavitationsbasierter Prozesse und stellt eine wichtige Erweiterung für bestehende und neue Ultraschallsysteme dar.
Keywords: Sonochemie; Akustische Kavitation; Kavitationsmessung; Kavitationsdetektion; FEM-Simulation Ultraschallwandler; Prozessüberwachung; FEM-Simulation Schallfeld; Self-Sensing; Piezoelektrische Ultraschallwandler; Ultraschallreinigung

Self-Stabilizing Supervised Publish-Subscribe Systems - Feldmann, Michael; Kolb, Christina; Scheideler, Christian; Strothmann, Thim Frederik (Proceedings of the 32nd IEEE International Parallel & Distributed Processing Symposium (IPDPS))
In this paper we present two major results: First, we introduce the first self-stabilizing version of a supervised overlay network (as introduced in~\cite{DBLP:conf/ispan/KothapalliS05}) by presenting a self-stabilizing supervised skip ring. Secondly, we show how to use the self-stabilizing supervised skip ring to construct an efficient self-stabilizing publish-subscribe system. That is, in addition to stabilizing the overlay network, every subscriber of a topic will eventually know all of the publications that have been issued so far for that topic. The communication work needed to processes a subscribe or unsubscribe operation is just a constant in a legitimate state, and the communication work of checking whether the system is still in a legitimate state is just a constant on expectation for the supervisor as well as any process in the system.
Keywords: Topological Self-stabilization; Supervised Overlay; Publish-Subscribe System

A Self-Stabilizing Hashed Patricia Trie - Knollmann, Till; Scheideler, Christian (Proceedings of the 20th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS))
While a lot of research in distributed computing has covered solutions for self-stabilizing computing and topologies, there is far less work on self-stabilization for distributed data structures. Considering crashing peers in peer-to-peer networks, it should not be taken for granted that a distributed data structure remains intact. In this work, we present a self-stabilizing protocol for a distributed data structure called the hashed Patricia Trie (Kniesburges and Scheideler WALCOM'11) that enables efficient prefix search on a set of keys. The data structure has a wide area of applications including string matching problems while offering low overhead and efficient operations when embedded on top of a distributed hash table. Especially, longest prefix matching for $x$ can be done in $\mathcal{O}(\log |x|)$ hash table read accesses. We show how to maintain the structure in a self-stabilizing way. Our protocol assures low overhead in a legal state and a total (asymptotically optimal) memory demand of $Θ(d)$ bits, where $d$ is the number of bits needed for storing all keys.
Keywords: Self-Stabilizing; Prefix Search; Distributed Data Structure

Intelligent Production of Wire Bonds using Multi-Objective Optimization – Insights, Opportunities and Challenges - Unger, Andreas; Hunstig, Matthias; Meyer, Tobias; Brökelmann, Michael; Sextro, Walter (In Proceedings of IMAPS 2018 – 51st Symposium on Microelectronics, Pasadena, CA, 2018)
Ultrasonic wire bonding is an indispensable process in the industrial manufacturing of semiconductor devices. Copper wire is increasingly replacing the well-established aluminium wire because of its superior electrical, thermal and mechanical properties. Copper wire processes differ significantly from aluminium processes and are more sensitive to disturbances, which reduces the range of parameter values suitable for a stable process. Disturbances can be compensated by an adaption of process parameters, but finding suitable parameters manually is difficult and time-consuming. This paper presents a physical model of the ultrasonic wire bonding process including the friction contact between tool and wire. This model yields novel insights into the process. A prototype of a multi-objective optimizing bonding machine (MOBM) is presented. It uses multi-objective optimization, based on the complete process model, to automatically select the best operating point as a compromise of concurrent objectives.
Keywords: wire bonding; multi-objective optimization; process model; copper wire; self-optimization

Reconsidering interiorization: Self moving across language spacetimes - Bertau, Marie-Cécile; Karsten, Andrea (New Ideas in Psychology)
Sociogenesis addresses a pervasive problem in psychology given by Cartesian dualism that assigns the mental an inner locus apart from material activity. Aligning ourselves to the ongoing critical discussions of interiorization in psychology, we explore the crucial notion of space by highlighting language as sociocultural and dialogical activity performed by other-oriented individuals. We discuss space in terms of the “language spacetime”, a symbolic, embodied formation of mutually positioned speaking and listening selves. This leads beyond the “inside-outside” container metaphor and allows for a reformulation of interiorization. Interiorization is conceptualized as a continuous series of different, though mutually related movements between self and other and self and self that lead to and are supported by specific formations in language activity: reversion, transposition, and decoupling. Along a short passage of a video-based interview, we trace the reversion of dialogical positions within the addressivity constellation of the two interlocutors, their interactive creation of a heterotopic spacetime, and the decoupling of one speaker's psychological activity from the concrete here-and-now and the present other by moving and acting into this new sphere. Interiorization appears as a movement at the border of past, present, and possible future(s).
Keywords: Interiorization; Dialogical self; Language activity; Voice; Vygotsky; Heterotopia; Video-confrontation

Optimization-based reliability control of mechatronic systems - Meyer, Tobias
Reliability-adaptive systems allow an adaptation of system behavior based on current system reliability. They can extend their lifetime at the cost of lowered performance or vice versa. This can be used to adapt failure behavior according to a maintenance plan, thus increasing availability while using up system capability fully. To facilitate setup, a control algorithm independent of a degradation model is desired. A closed loop control technique for reliability based on a health index, a measure for system degradation, is introduced. It uses self-optimization as means to implement behavior adaptation. This is based on selecting the priorities of objectives that the system pursues. Possible working points are computed beforehand using model-based multiobjective optimization techniques. The controller selects the priorities of objectives and this way balances reliability and performance. As exemplary application, an automatically actuated single plate dry clutch is introduced. The entire reliability control is setup and lifetime experiments are conducted. Results show that the variance of time to failure is reduced greatly, making the failure behavior more predictable. At the same time, the desired usable lifetime can be extended at the cost of system performance to allow for changed maintenance intervals. Together, these possibilities allow for greater system usage and better planning of maintenance.
Keywords: dependability; reliability; behavior adaptation; self-optimization; multiobjective optimization; optimal control; automotive drivetrain; clutch system; reliability-adaptive system

Experiential or Self-Regulated Learning: A Critical Reflection of Entrepreneurial Learning Processes - Fust, Alexander Paul; Jenert, Tobias; Winkler, Christoph (Entrepreneurship Research Journal)
Research on entrepreneurial learning highlights the importance of experience and prior knowledge to entrepreneurial success. However, a conundrum remains and we are still seeking answers as to why some novice entrepreneurs learn successfully from their experiences and succeed, while some experienced entrepreneurs fail with their ventures. In order to advance the discussion about the role of experience during entrepreneurial learning, our critical reflection aims to (1) highlight some of the shortcomings of experiential learning theory (ELT) and (2) illustrate how alternative theoretical perspectives have the potential to advance our conceptual understanding of entrepreneurial learning processes. We argue for an explanation of entrepreneurial learning as a dynamic and self-regulated process that relies on planning, monitoring, and self-reflection.
Keywords: entrepreneurial learning; experiential learning; self-regulated learning

Estimation of Remaining Useful Lifetime of Piezoelectric Transducers Based on Self-Sensing - Kimotho, James Kuria; Sextro, Walter; Hemsel, Tobias (IEEE Transactions on Reliability)
Piezoelectric transducers are used in a wide range of applications. Reliability of these transducers is an important aspect in their application. Prognostics, which involve continuous monitoring of the health of technical systems and using this information to estimate the current health state and consequently predict the remaining useful lifetime (RUL), can be used to increase the reliability, safety, and availability of the transducers. This is achieved by utilizing the health state and RUL predictions to adaptively control the usage of the components or to schedule appropriate maintenance without interrupting operation. In this work, a prognostic approach utilizing self-sensing, where electric signals of a piezoelectric transducer are used as the condition monitoring data, is proposed. The approach involves training machine learning algorithms to model the degradation of the transducers through a health index and the use of the learned model to estimate the health index of similar transducers. The current health index is then used to estimate RUL of test components. The feasibility of the approach is demonstrated using piezoelectric bimorphs and the results show that the method is accurate in predicting the health index and RUL.
Keywords: Estimation of Remaining Useful Lifetime of Piezoelectric Transducers Based on Self-Sensing

Evolvable caches: Optimization of reconfigurable cache mappings for a LEON3/Linux-based multi-core processor - Ho, Nam; Kaufmann, Paul; Platzner, Marco (2017 International Conference on Field Programmable Technology (ICFPT))
Keywords: Linux; cache storage; microprocessor chips; multiprocessing systems; LEON3-Linux based multicore processor; MiBench suite; block sizes; cache adaptation; evolvable caches; memory-to-cache-index mapping function; processor caches; reconfigurable cache mapping optimization; reconfigurable hardware technology; replacement strategies; standard Linux OS; time a complete hardware implementation; Hardware; Indexes; Linux; Measurement; Multicore processing; Optimization; Training

Computational self-awareness as design approach for visual sensor nodes - Guettatfi, Zakarya; Hübner, Philipp; Platzner, Marco; Rinner, Bernhard (12th International Symposium on Reconfigurable Communication-centric Systems-on-Chip (ReCoSoC))
Keywords: embedded systems; image sensors; power aware computing; wireless sensor networks; Zynq-based VSN node prototype; computational self-awareness; design approach; platform levels; power consumption; visual sensor networks; visual sensor nodes; Cameras; Hardware; Middleware; Multicore processing; Operating systems; Runtime; Reconfigurable platforms; distributed embedded systems; performance-resource trade-off; self-awareness; visual sensor nodes

Linking Services to Websites by Leveraging Semantic Data - Wolters, Dennis; Heindorf, Stefan; Kirchhoff, Jonas; Engels, Gregor (2017 IEEE International Conference on Web Services (ICWS))
Websites increasingly embed semantic data for search engine optimization. The most common ontology for semantic data, schema.org, is supported by all major search engines and describes over 500 data types, including calendar events, recipes, products, and TV shows. As of today, users wishing to pass this data to their favorite applications, e.g., their calendars, cookbooks, price comparison applications or even smart devices such as TV receivers, rely on cumbersome and error-prone workarounds such as reentering the data or a series of copy and paste operations. In this paper, we present Semantic Data Mediator (SDM), an approach that allows the easy transfer of semantic data to a multitude of services, ranging from web services to applications installed on different devices. SDM extracts semantic data from the currently displayed web page on the client-side, offers suitable services to the user, and by the press of a button, forwards this data to the desired service while doing all the necessary data conversion and service interface adaptation in between. To realize this, we built a reusable repository of service descriptions, data converters, and service adapters, which can be extended by the crowd. Our approach for linking services to websites relies solely on semantic data and does not require any additional support by either website or service developers. We have fully implemented our approach and present a real-world case study demonstrating its feasibility and usefulness.
Keywords: Services; Websites; Semantic Data; schema.org; Data Conversion; Interface Adaptation; Mediation

Self-Adjusting Monitor for Measuring Aging Rate and Advancement - Sadeghi-Kohan, Somayeh; Kamal, Mehdi; Navabi, Zainalabedin (IEEE Transactions on Emerging Topics in Computing)
Time-variant age information of different parts of a system can be used for system-level performance improvement through high-level task scheduling, thus extending the life-time of the system. Progressive age information should provide the age state that the system is in, and the rate that it is being aged at. In this paper, we propose a structure that monitors certain paths of a circuit and detects its gradual age growth, and provides the aging rate and aging state of the circuit. The proposed monitors are placed on a selected set of nodes that represent a timing bottleneck of the system. These monitors sample expected data on these nodes, and compare them with the expected values. The timing of sampling changes as the circuit ages and its delay increases. The timing of sampling will provide a measure of aging advancement of a circuit. To assess the efficacy of the proposed method and compare it with other state-of-the-art aging monitors, we use them on selected nodes of the execution unit of different processors, as well as some circuits from ITC99 benchmarks. The results reveal that the precision of our proposed method is between 0.12 (ns) to 0.401 (ns). Its Area and power overhead are negligible and are about 2.13 and 0.69 percent respectively.
Keywords: Age advancement; age monitoring clock; aging rate; self-adjusting monitors

Reliable Manufacturing of Heavy Copper Wire Bonds Using Online Parameter Adaptation - Meyer , Tobias; Unger, Andreas; Althoff, Simon; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias; Guth, Karsten (IEEE 66th Electronic Components and Technology Conference)
Usage of copper wire bonds allows to push power boundaries imposed by aluminum wire bonds. Copper allows higher electrical, thermal and mechanical loads than aluminum, which currently is the most commonly used material in heavy wire bonding. This is the main driving factor for increased usage of copper in high power applications such as wind turbines, locomotives or electric vehicles. At the same time, usage of copper also increases tool wear and reduces the range of parameter values for a stable process, making the process more challenging. To overcome these drawbacks, parameter adaptation at runtime using self-optimization is desired. A self-optimizing system is based on system objectives that evaluate and quantify system performance. System parameters can be changed at runtime such that pre-selected objective values are reached. For adaptation of bond process parameters, model-based self-optimization is employed. Since it is based on a model of the system, the bond process was modeled. In addition to static model parameters such as wire and substrate material properties and vibration characteristics of transducer and tool, variable model inputs are process parameters. Main simulation result is bonded area in the wiresubstrate contact. This model is then used to find valid and optimal working points before operation. The working point is composed of normal force and ultrasonic voltage trajectories, which are usually determined experimentally. Instead, multiobjective optimalization is used to compute trajectories that simultaneously optimize bond quality, process duration, tool wear and probability of tool-substrate contacts. The values of these objectives are computed using the process model. At runtime, selection among pre-determined optimal working points is sufficient to prioritize individual objectives. This way, the computationally expensive process of numerically solving a multiobjective optimal control problem and the demanding high speed bonding process are separated. To evaluate to what extent the pre-defined goals of self-optimization are met, an offthe- shelf heavy wire bonding machine was modified to allow for parameter adaptation and for transmitting of measurement data at runtime. This data is received by an external computer system and evaluated to select a new working point. Then, new process parameters are sent to the modified bonding machine for use for subsequent bonds. With these components, a full self-optimizing system has been implemented.
Keywords: Self-optimization; adaptive system; bond process; copper wire

Self-Aware and Self-Expressive Systems – Guest Editor's Introduction - Torresen, Jim; Plessl, Christian; Yao, Xin (IEEE Computer)
Keywords: self-awareness; self-expression

The Value of Self-Service: Long-Term Effects of Technology-Based Self-Service Usage on Customer Retention. - Scherer, Anne; Wünderlich, Nancy; Von Wangenheim, Florian (MIS Quarterly)
Advancements in information technology have changed the way customers experience a service encounter and their relationship with service providers. Especially technology-based self-service channels have found their way into the 21st century service economy. While research embraces these channels for their cost-efficiency, it has not examined whether a shift from personal to self-service affects customer–firm relationships. Drawing from the service-dominant logic and its central concept of value-in-context, we discuss customers’ value creation in self-service and personal service channels and examine the long-term impact of these channels on customer retention. Using longitudinal customer data, we investigate how the ratio of self-service versus personal service use influences customer defection over time. Our findings suggest that the ratio of self-service to personal service used affects customer defection in a U-shaped manner, with intermediate levels of both self-service and personal service use being associated with the lowest likelihood of defection. We also find that this effect mitigates over time. We conclude that firms should not shift customers toward self-service channels completely, especially not at the beginning of a relationship. Our study underlines the importance of understanding when and how self-service technologies create valuable customer experiences and stresses the notion of actively managing customers’ cocreation of value.
Keywords: customer defection; customer retention; e-service; longitudinal; Self-service; value-in-context